2017
DOI: 10.1007/s10897-017-0160-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Expanded Carrier Screening: Reproductive Behaviors of At‐Risk Couples

Abstract: Expanded carrier screening (ECS) analyzes dozens or hundreds of recessive genes to determine reproductive risk. Data on the clinical utility of screening conditions beyond professional guidelines are scarce. Individuals underwent ECS for up to 110 genes. Five-hundred thirty-seven at-risk couples (ARC), those in which both partners carry the same recessive disease, were invited to participate in a retrospective IRB-approved survey of their reproductive decision making after receiving ECS results. Sixty-four eli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 18 publications
5
64
0
2
Order By: Relevance
“…Our previous study of carrier rates in 346 790 patients showed that an ECS panel was expected to identify more pregnancies at risk for serious conditions than ethnic-based panels spanning far fewer genes (4 ), and the American College of Obstetricians and Gynecologists recently recognized ECS as an acceptable strategy for preconception and prenatal carrier screening (5 ). To the extent that these guidelines increase ECS usage, they will have a large clinical impact because it has recently been shown in clinical-utility studies that approximately 80% of couples found to be at risk for severe conditions pursue alternative reproductive options (6,7 ).…”
Section: © 2018 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Our previous study of carrier rates in 346 790 patients showed that an ECS panel was expected to identify more pregnancies at risk for serious conditions than ethnic-based panels spanning far fewer genes (4 ), and the American College of Obstetricians and Gynecologists recently recognized ECS as an acceptable strategy for preconception and prenatal carrier screening (5 ). To the extent that these guidelines increase ECS usage, they will have a large clinical impact because it has recently been shown in clinical-utility studies that approximately 80% of couples found to be at risk for severe conditions pursue alternative reproductive options (6,7 ).…”
Section: © 2018 American Association For Clinical Chemistrymentioning
confidence: 99%
“…While many couples undergo prenatal ECS, preconception screening was the focus of our model because it has well established utility and confers greater patient autonomy 2 . We expect similar results at either stage but with a reduced rate of reproductive interventions for prenatal screening 10 . Importantly, even if the intervention rate were to drop from its 76% preconception value to 50% in the prenatal period (as was observed in the post-conception cohort in 10 ), our one-way sensitivity analysis demonstrated that ECS would still avert 150 births affected with severe disease and $2,000 in lifetime cost per birth.…”
Section: Discussionmentioning
confidence: 62%
“…Second, we assume that the detection rate for each condition is 100% (see Discussion), so that couples deemed "not at risk" have zero chance of having a child affected with a screened condition (see Discussion). Third, at-risk couples (ARCs; defined below) have a fixed probability of choosing a reproductive intervention that is assumed to avert any possibility of a child affected by a screened condition; this fixed probability (76%) is estimated from survey-based clinical utility studies of ARCs 10,11 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations